Criminal Policy as an Effort to Overcome the Criminal Act of Theft of Plantation Products during the Covid-19 Period Through the Criminal Law (Study of PTPN III-(Persero)) - Herlina Manullang (LEGAL BRIEF, 2022)
Criminal acts in Indonesia have increased during the COVID-19 pandemic which caused unrest in the community. One of the most common types of criminal acts during the Covid-19 pandemic is the crime of theft, all of which cause many layoffs. During 2019-2021, the number of thefts of plantation products in PTPN III during the Covid-19 pandemic increased significantly. The type of research used is empirical juridical research, while the source of legal materials used is primary legal materials and secondary source legal materials. The factors that cause the criminal act of theft of plantation products in the territory of PTPN III PERSERO are economic factors, educational factors, environmental factors, global development factors and law enforcement factors. Efforts to combat the theft of plantation products are carried out by penal and non-penal means.